Pengaruh Konsumsi Listrik, Konsumsi Bahan Bakar dan Konsumsi Gas Terhadap Pertumbuhan Ekonomi di Indonesia - Hafizhulhuda; Sri Ulfa Sentosa (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This study aims to determine and analyze how the impact of electricity consumption, fuel consumption and gas consumption on economic growth in Indonesia. This research is descriptive and associative, namely research that explains the research variables and tests whether there is an influence between the independent and dependent variables. This research analyzes 3 independent variables using secondary data in the form of time series data for 30 years from 1992 to 2021. The analytical tool used is multiple regression analysis with the Ordinary Least Square (OLS) method to process this data using the Eviews12 program. The research results show that the independent variables, namely electricity consumption, fuel consumption and gas consumption together, have no effect on the dependent variable, namely economic growth. Partially, it shows that the electricity consumption The electricity consumption variable has a positive but insignificant influence on economic growth, the fuel consumption variable has a negative and insignificant influence on economic growth, and the gas consumption variable has a negative and insignificant influence on economic growth. The results of the classical assumption test from this research show that the regression model is free from symptoms of multicollinearity, autocorrelation and heteroscedasticity.